Zoonotic diseases in Zambian goat herds : prevalence and risk factors - Karlsson Bergkvist, Pernilla (SLU/Dept. of Clinical Sciences (until 231231), 2020)
Small ruminants play an important role in low-income countries due to their ability to bring food and income to their owners. Loss of these animals due to disease can therefore affect a family’s ability to support their livelihood and the children’s opportunities to go to school so that they can improve their future. The aim of this study was to investigate the prevalence of three zoonotic diseases among goats that can have an impact on both animal health and production and human health: brucellosis, Crimean-Congo haemorrhagic fever (CCHF) and Rift Valley fever (RVF). Another aim was to find associations between the seroprevalence of the disease and management routines to see if there were any specific risk factors to contracting the diseases in the herds. Serum samples were collected from goats in three districts in the Central and Southern provinces of Zambia, more specifically Monze and Mazabuka in the Southern province, and Chibombo district in Central province. In each district, ten villages were randomly selected and in each village four households with at least four goats were visited for sampling. The farmers in each household were interviewed using a questionnaire with questions regarding management routines and details about the animals. After sampling the serum was analysed for antibodies to the selected diseases using commercially available specific ELISA kits. To find associations between the seroprevalence and management routines, Fisher’s exact test was used. No individuals were found to have RVF antibodies. The prevalence of CCHF was found to be 5.2% and seroprevalence of brucellosis was 2.7%. Association was found between being CCHF seropositive and having contact with other cattle herds equal to or more often than every six months. No other associations could be found between seropositive animals and management routines.